The Voiceless Citizens in James Kelman’s Translated Accounts - Alrayes, Fadi Mumtaz Yousif; Alkass Yousif, Anan J Lewis (Al-Adab Journal, 2022)
The purpose of this paper is to underline James Kelman’s voiceless working class figures in a cosmopolitan world, arguing that the peripheral and unprivileged part of Scotland is the very factor that reconstructs the modern diverse reality of Scottish culture. This article discusses Kelman’s Translated Accounts and shows how the peripheral live under a state of oppression deprived from their individual freedom and individuality where fear and anxiety hunt his characters. Translated Accounts is a novel about two unnamed group, but they represent two poles: the privileged and the periphery. Though the novel depicts unknown characters and setting, one might immediately make the connection between the unfair living condition of the Scottish working class individual and these hidden figures. Interestingly, Kelman’s choose to make his characters and setting anonymous is to add a cosmopolitan notion that the oppression of the periphery is still all over the world.